"Features of Far North Life Pictured by the Bartlett-Academy of Natural Sciences Greenland Expedition" (Philadelphia Evening Bulletin, 1930)
"Harry Whitney, representative of the Academy of Natural Sciences, on the Bartlett-Academy Expedition, is shown feeding bottled milk to muscle-ox calves on the Morrissey. These animals, after a quarantine, will be brought here and other specimens are to be mounted in a habitat group in the Academy Museum, now being modernized." With clipping